Pengaruh Tingkat Pendidikan dan Modal Usaha Terhadap Kinerja UMK - Mayang Hesti Putri; Marwan Marwan (Universitas Negeri Padang, 2023)
This study aims to determine the effect of education level, and working capital on the performance of MSEs. This type of quantitative research uses a correlation research design with causal associative methods. The population in this study found 32 people. The sampling technique used was total sampling, which is a sampling technique that provides equal opportunities for each member of the population to be selected as members of the sample, while the number of samples in this study was 32 people. Data were collected using a questionnaire. Furthermore, to examine the effect of the given treatment, we utilized the IBM SPSS software. Based on the results of data analysis shows that: (1) Education level has a significant effect on MSE performance (2) Business capital has a significant effect on MSE performance, (3) Education level and working capital simultaneously have a significant effect on MSE performance